Đề xuất quy trình dạy học học phần tổ chức hoạt động giáo dục STEAM cho sinh viên đại học ngành Giáo dục mầm non - Đinh, Lan Anh; Hoàng, Thanh Thúy; Đặng, Đặng Lan Phương (Tạp chí Giáo dục, 2025)
Organizing STEAM educational activities for students majoring in Early Childhood Education plays a key role in meeting the professional requirements of future teachers and adapting to the development of modern society. Although the course “Organizing STEAM educational activities” has been implemented at a number of universities, due to its new nature, the development of a teaching process for this course is still an urgent requirement. Based on pedagogical principles, the article proposes a 5-step teaching process for this course aiming to develop the capacity to organize STEAM activities for students, equipping them with knowledge, skills and effective integrated teaching methods. The proposed teaching process for the course “Organizing STEAM educational activities” can be used for experimental studies to improve the training efficiency of students majoring in Early Childhood Education in the context of current educational innovation.